Mechanochemical‐Triggered Confined Coordination of Iron‐Biomass Composites for Efficient Cr(VI) Reduction Under Circumneutral pH Via Accelerated Electron Extraction - Yue Wang; Hongyu Li; Hao Liu; Chengsi Hou; Zhengwei Zhou; Shuai Peng; Zuofeng Chen; Zhendong Lei; Deli Wu (Advanced Science)
Abstract Green and eco‐friendly iron‐based materials for efficient Cr(VI) removal have attracted considerable interest, but challenges related to narrow working pH ranges and iron utilization efficiency still remain. Herein, inspired by the hot‐spot effect‐triggered confined coordination strategy, a biomass‐confined iron‐based reductant (CMC‐GTB/Febm) is designed for Cr(VI) reduction and detoxification. Electron enrichment and confinement on biomass carriers are achieved through electron transfer mediated by coordination interactions between anchored iron species and biomass. Thus, the CMC‐GTB/Febm achieved 99% Cr(VI) reduction at circumneutral pH (5–9), with a maximum removal capacity of 180 mg g−1. Under iron dosing close to the stoichiometric ratio (Fe/Cr = 3/1), the Cr(VI) removal kinetics and efficiency of CMC‐GTB/Febm are 53.2–870.5 and 5.5–48.8 times higher than those of micro‐ or nano‐zero‐valent iron (ZVI), respectively. Mechanistic analyses revealed that confined electron transfer is facilitated by coordination interactions between biomass and anchored iron species, which enhanced Cr(VI) reduction. Moreover, biomass‐tethered reduced Cr(III) is stabilized by electrostatic adsorption and biomass‐Cr(III) coordination, which ultimately detoxifies the phytotoxicity of Cr(VI). The conversion of this strategy to kilogram‐scale production and the simulated Cr(VI) removal in real water matrices are confirmed. This study provides a basis for the controlled design and industrial application of environmentally friendly iron‐based reductants.